Factors Contributing to Dry Weight Differences Among Herbivorous Zooplankton in Two Softwater Lakes - Campbell, Lisa (My University, 1994)
The dry weight of zooplankton is an important parameter conventionally used to estimate secondary production in aquatic ecosystems. Estimates of zooplankton weight vary considerably across studies. This study examines various factors that contribute to differences in the individual dry weight of freshwater herbivorous zooplankton. In the first chapter, I quantified and compared the individual length and weight changes of Daphnia catawba and Diaptomus minutus resulting from preservation in either 4% sugar-formalin, 70% ethanol solution or freezing over dry ice. The results indicate that the dry weight of both animals was significantly altered by chemical preservatives. The length of Diaptomus was also significantly reduced due to preservation. Site-specific differences in lakes, such as available food and the presence of predators, introduce another potential source of variation in herbivore dry weight. In Chapter 2, the food available to several herbivorous zooplankton in two softwater lakes was estimated using various methods. An index of "edible" phytoplankton biomass based on stomach content analyses was developed and compared to the traditional techniques used to estimate available food. The results indicate that the available was food different for each herbivore and that estimates of food available based on stomach content analyses were not significantly related to the traditional techniques used to estimate available food. In Chapter 3, I evaluate the relative impacts of "topdown" (predation) versus "bottom-up" (food) effects on the dry weight of several herbivores in two softwater lakes with contrasting food-web structures. The length-specific dry weights of Daphnia catawba, Diaptomus minutus and Holopedium gibberum varied seasonally and these changes were taxa-specific and unique to each lake. Herbivore weights were regressed against length, available food, clutch size, population density and temperature to determine if "bottom-up" effects could explain between-lake differences in herbivore weight. Length and population density were the prominent predictor variables in the resulting regression models for the herbivores in these lakes. Predator effects were determined by comparing if the between-lake differences in herbivore weight were consistent with the presence or absence of planktivores. Holopedium dry weight was lower in the presence of planktivores, while Diaptomus dry-weight differences exhibited no consistent trend with the presence or absence of planktivores.
Keywords: weight; herbivore; zooplankton; softwater; lake